2021
DOI: 10.1007/s13555-021-00591-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Novel Formulation of Clobetasol Propionate 0.025% Cream in Indian Moderate-to-Severe Psoriasis Patients: Phase-2a, Randomized 3-Arm Study

Abstract: Introduction: Clobetasol propionate (0.05% standard dose formulation), a topical corticosteroid, leads to systemic side-effects like hypothalamic-pituitary-adrenal (HPA) axis suppression at doses as low as 2 g/day. The aim of this study was to evaluate HPA axis suppression, efficacy, and safety of clobetasol propionate (0.025%, formulation 5 and 13) versus currently marketed 0.05% cream in Indian patients with moderate-to-severe psoriasis. Methods: In this phase 2a investigator-blinded study, patients aged C 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The global prevalence of psoriasis ranges from 0.09-11.43%, resulting in a high global burden that significantly hampers the quality of life. 3 Since the introduction of TCs, they serve a central position in the management of various skin disorders such as psoriasis, contact dermatitis, seborrheic dermatitis, atopic dermatitis, and other inflammatory dermatological conditions. 1 Class 1 TCs are prescribed by dermatologists for the treatment of plaque psoriasis in approximately 60% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global prevalence of psoriasis ranges from 0.09-11.43%, resulting in a high global burden that significantly hampers the quality of life. 3 Since the introduction of TCs, they serve a central position in the management of various skin disorders such as psoriasis, contact dermatitis, seborrheic dermatitis, atopic dermatitis, and other inflammatory dermatological conditions. 1 Class 1 TCs are prescribed by dermatologists for the treatment of plaque psoriasis in approximately 60% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of improved formulations containing half the concentration of conventional CP (0.025%) without compromising on the therapeutic potential and safety will cater to the unmet needs. 3 The success or failure of a TC is largely impacted by vehicle formulation and patient preference, along with its potency and anticipated efficacy. CP 0.025% is class I TC developed as a cream formulation without propylene glycol, ethanol, and a sorbitol-based emulsifier like sorbitan sesquioleate, which is a contact allergen and a common component in several TC formulations, including the CP 0.05% ointment.…”
mentioning
confidence: 99%
“…The results of the study revealed that PGA success rates (clear or almost clear), at the end of the treatment, were higher with 0.025% formulations and were as follows: 5 (38.9%) and 13 (36.8%) versus 0.05% cream (30.8%). 8 In another phase II study conducted in United States, Draelos et al compared the efficacy of CP 0.025% cream versus CP 0.05% cream in patients (≥18 years) with a clinical diagnosis of stable (at least 3 months) plaquetype psoriasis, that involved 20% to 50% of the BSA (Investigator Global Assessment (IGA) grade of at least 3). The patients used either CP 0.025% cream or CP 0.05% cream for 15 consecutive days.…”
Section: Efficacy and Potencymentioning
confidence: 99%
“…CP is the strongest topical steroid approved for use. 2 It inhibits cytokine production and has anti-inflammatory, immunosuppressive, and antimitotic activities. It also alters the growth, differentiation, and function of diverse cells.…”
Section: Introductionmentioning
confidence: 99%